Development of e-LKPD Based on Integrated PBL STEM Material on Electrolyte and Non-Electrolyte Solutions Oriented to Critical Thinking Skills of High School Students - Rara Utami; Muhammad Naswir; Wilda Syahri (Mathematics Education Study Program, 2025)
The goal of this research is to create eLKPD that utilizes ProblemBased Learning (PBL) combined with STEM, focusing on electrolyte and nonelectrolyte solutions, with the intention of enhancing critical thinking abilities in students. Additionally, the study seeks to assess the practicality of the eLKPD that incorporates PBL and STEM, based on evaluations from experts in content and media, along with feedback from teachers and students regarding the developed eLKPD. The research follows the Lee & Owens (2004) model, which consists of five phases: analysis, design, development, implementation, and evaluation. The study involved a oneonone trial with 3 students and a small group trial with 10 students at SMAN 2 Muaro Jambi. Qualitative and quantitative analysis methods were employed for data examination. Findings indicated that the created eLKPD, based on PBL integrated with STEM, was deemed both feasible and valid, scoring an average of 4. 75 for material and media validation, and 4. 6 overall. An average score of 4. 66 was recorded for teacher assessments. In the oneonone trial, participants achieved a score of 29, translating to a percentage of 96. 66%. For the small group trial, the total score was 462, with a percentage of 92. 4%. Furthermore, the evaluation results of students' critical thinking showed an average score of 79. 76, with a completion rate of 77%. As a result of these findings, the eLKPD created was confirmed to be valid and practical for educational purposes, receiving positive feedback from students